Guideline adherence and patient satisfaction in the treatment of inflammatory bowel disorders - an evaluation study - Holtmann Gerald; Gesenhues Stefan; Haag Sebastian; Pieper Claudia; Gerken Guido; Jöckel Karl-Heinz (BMC, 2009)
Abstract Background Crohn's disease (CD) and ulcerative colitis (UC) are the most frequent inflammatory bowel disorders (IBD). IBD cause a significant burden to society due to extensive health care utilization from the first clinical symptoms until diagnosis and thereafter due to direct and indirect costs. Besides the socio-economic impact of CD and UC, gastrointestinal and extraintestinal symptoms affect quality of life, but there is remarkably little data about the quality of treatment as assessed by patient satisfaction, quality of life and adherence to guidelines. Thus the aim of this study was to identify variables that influence quality of treatment and quality of life as well as patient satisfaction. Methods The Essener Zirkel Study was a cross sectional study of 86 IBD-patients with a confirmed diagnosis of CD or UC. They were recruited at primary, secondary and tertiary care settings. Quality of treatment, quality of life and patient satisfaction were evaluated. Consulting behaviour and number of examinations, duration of disease and variables regarding adherence to guidelines were evaluated, too. Results 59 (69%) patients had CD and 27 had UC (31%). 19% spent more than four years until the suspected diagnosis of IBD was confirmed and visited more than five physicians. All patients showed a significantly reduced quality of life compared to the 1998 German normative population. In spite of being under medical treatment, nearly half of the patients suffered from strong quality of life restricting symptoms. Over all, 35% described their treatment as moderate or bad. Patients who consulted psychotherapists and non-medical practitioners suffered significantly less from depression. Conclusion Besides structural deficiencies due to the health care policy, we revealed the adherence to guidelines to be a problem area. Our findings support the assumption, that providing better health care and especially maintaining constant patient-physician communication improves patient satisfaction.